DPPH and Hep2 Cell Inhibitions by Ethyl Acetate Extract and Its Fractions from Indonesian Cassia siamea L. Stem Barks: In Vitro and Computational Prediction - Hasballah, Kartini; Murniana, Murniana; Marlina, Marlina; Bakhtiar , Bakhtiar; Rusly, Dewi Karlina; Ginting, Binawati; Maidiani, Tika; Rahmazani, Shinta; Rampengan, Derren DCH (Science and Technology Indonesia, 2026)
Cassia siamea has been reported by multiple ethnopharmacological studies to treat a broad spectrum of diseases, including cancer. The aim of this study was to evaluate the antioxidant and antiproliferation activities of C. siamea stem bark extract. Following the maceration, the sample was fractionated using column chromatography, yielding 1 ethyl acetate extract and 4 different fractions (Fractions A–D). Antioxidant activities of the extract and its four fractions were assessed based on the 2,2-diphenyl-1-picrylhydrazyl (DPPH) inhibition. Phytocompounds contained in the extract and its fractions were identified using Gas Chromatography-Mass Spectrometry (GC/MS) analysis, followed by in silico molecular docking. The ethyl acetate extract of C. siamea L. stem bark had total phenolic, flavonoid, and tannin contents of 280 mg GAE/g dry extract, 23.97 mg QE/g dry extract, and 26.5 mg TAE/ g dry extract, respectively. Strong antioxidant activities were exhibited by Fraction A and the ethyl acetate extract (IC50= 13.72 and 14.10, respectively). LC50s of the ethyl acetate extract and Fraction A against the A. salina larvae were 49.61 ppm and 51.52 ppm, respectively. Optimal inhibitions of Hep2 cell proliferation were observed in both ethyl acetate extract and Fraction A with IC50s of 936.34 ppm and 580.76 ppm, respectively. Both the extract and Fraction A contained lupeol, among other compounds with anticancer potential. Complementary in silico docking analyses indicated that lupeol achieved optimal binding with laryngeal carcinoma–related targets (ΔG = –7.9 to 9.5 kcal/mol).